The possible impairment of respiratory‐related neural loops may be associated with the silent pneumonia induced by SARS‐CoV‐2 - Tan, Bai‐Hong (J Med Virol, 2020)
As compared to many other viral pulmonary infections, there existed several peculiar manifestations in the COVID‐19 patients, including the “silence” of pneumonia in both mild and severe cases and a long intensive care unit stay for those requiring invasive mechanical ventilation. Similar silent pneumonia has been documented in the infectioninduced by H5N1 influenza virus HK483 and was found to result from the direct attack of the virus on the bronchopulmonary C‐fibers at the early stage and the final infection in the brainstem at the late stage. The long stay of critical patients in the intensive care unit is possibly due to the depression of central respiratory drive, which resulted in the failure to wean from the mechanic ventilation. Carotid and aortic bodies and bronchopulmonary C‐fibers are two key peripheral components responsible for the chemosensitive responses in the respiratory system, while triggering respiratory reflexes depends predominantly on the putative chemosensitive neurons located in the pontomedullary nuclei. In view of the findings for the H5N1 influenza virus, the silence of pneumonia induced by SARS‐CoV‐2 may be due to the possible impairment of peripheral chemosensitive reflexes as well as the damage to the respiratory‐related central neurons.